ANALISIS STRATEGI PROMOSI PADA PRODUK GADAI EMAS DAN CICIL EMAS PADA PERUSAHAAN PEGADAIAN KOTA DAN BANK SYARIAH INDONESIA KCP MANDAILING NATAL - Nanda Kurniawan Lubis (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
Pawning gold at BSI KCP Mandailing this Christmas has challenges in marketing its products, where people know more about pawning, namely at city sharia pawnshops. BSI KCP Mandailing Natal itself has a strategy to attract customer interest by carrying out various efforts and strategies. The Gold Pawn or Installment product, which is a unique product from BSI Bank, recorded fund management income as mudharib of IDR 425.58 billion, an increase of 11.61% from the 2020 position of IDR 381.29 billion. Likewise, other business revenues were recorded to have increased by 15.10% to IDR 71.99 billion compared to 2020 which amounted to IDR 62.54 trillion. Based on recorded data, income from gold pawning always experiences increasing progress. The aim of this research is to analyze the marketing strategy for gold pawn products at BSI KCP Mandailing Natal.This research uses qualitative research with descriptive methods. The data collection technique used in the research was by conducting interviews and documentation with gold pawn employees at Pegadaian Syaraiah Kota and BSI KCP Mandailing Natal. Next, the data will be processed and analyzed using descriptive methods.The results of this research show that BSI BSI KCP Mandailing Natal's strategy in marketing gold pawn products uses a 4P marketing mix, namely (product, price, place, promotion). To achieve marketing objectives in terms of products, Pegadaian Syaraiah Kota and BSI KCP Mandailing Natal are developing gold pawn products into products that are in demand by customers and can be taken over, in terms of price, BSI KCP Mandailing Natal provides low administration fees and rental fees, in terms of location, Pegadaian Syaraiah Kota and BSI KCP Mandailing Natal are very strategic and easy to reach in terms of promotion, they are quite good at marketing products, offline and online, including offline (placing banners, word of mouth, visiting agencies) and some also use personal selling, while online promoting gold pawning through social media such as (Instagram, Facebook, Whatsapp, Tiktok). Strategy of Bank Syariah Indonesia KCP Mandailing Natal in marketing gold pawn products using a 4P marketing mix, namely (product, price, place, promotion) to achieve marketing objectives in terms of products, in terms of promotion it is quite good in marketing the product, with offline and online methods, offline includes (placing banners, word of mouth and visiting agencies) and some also use personal selling while online promotes gold pawning through social media such as (Instagram, Facebook, Whatsapp). Meanwhile, in the promotion carried out by Pegadaian Syariah Kota district. Mandailing Natal with a 7P marketing system, namely Product, Price, promotion, place, people, physical evidence and process